Return Migrants and the Wage Premium: Does the Legal Status of Migrants Matter? - Nelly Elmallakh; Jackline Wahba (Institute of Labor Economics (IZA), 2021)
This paper examines the impact of the legal status of overseas migrants on their wages upon return to the home country. Using unique data from Egypt, which allows us to distinguish between return migrants according to their type of international migration, documented versus undocumented, we examine the impact of the illegal status on wages upon return. Relying on a conditional mixed process model, which takes into account the selection into emigration, into return, and into the legal status of temporary migration, we find that, upon return, undocumented migrants witness a wage penalty compared to documented migrants, as well as relative to non-migrants. Our results are the first to show the impact of undocumented migration on the migrant upon return to the country of origin.
Keywords: F22; J30; 330; return migration; undocumented migration; illegality; wages; Egypt